Electro-synthesized Co(OH)2@CoSe with Co–OH active sites for overall water splitting electrocatalysis. Issue 2 (16th January 2020) - Wang, Yin; Yang, Yutong; Wang, Xia; Li, Peihe; Shao, Hongyang; Li, Tianen; Liu, Haiyang; Zheng, Qingfu; Hu, Jing; Duan, Limei; Hu, Changwen; Liu, Jinghai
Abstract : An in situ electrochemical transformation strategy has been rationally designed to fabricate Co(OH)2 @CoSe nanorods (NRs) for practical electrolytic overall water splitting. Abstract : Constructing noble metal-free electrocatalytically active sites for the simultaneous hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline solution is key to realizing electricity-driven water splitting in practical applications. Here, we rationally designed Co(OH)2 @CoSe nanorods (NRs) as an excellent bifunctional electrocatalyst by an in situ electrochemical transformation strategy, where the Co-based nanorod template was converted into Co(OH)2 @CoSe at the cathode. The obtained electrode exhibits superior electrocatalytic activity for both the HER (overpotential of 208 mV at 20 mA cm −2 ) and the OER (268 mV at 20 mA cm −2 ) at high current density in a 1 M KOH solution. The theoretical calculations and experimental evidence indicate that the chemical coupling Co–OH active site between Co(OH)2 and CoSe regulates the hydrogen adsorption and desorption energy and fast electron transfer capability, which is responsible for the improved HER. Moreover, the Co(OH)2 @CoSe NRs can be further converted into CoOOH nanosheets which serve as OER active sites. Toward practical electrolytic cell applications, the Co(OH)2 @CoSe nanorods as both the cathode and anode achieved a current density of 100 mA cm −2 at 1.94 V for overall water splitting, better than that of noble metal-based electrocatalysts.